2020
DOI: 10.3390/genes11121422
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Transcriptomic Analysis Identify Spliceosome as a Significant Component of the Molecular Machinery in the Pituitary Tumors Derived from POU1F1- and NR5A1-Cell Lineages

Abstract: Background: Pituitary adenomas (PA) are the second most common tumor in the central nervous system and have low counts of mutated genes. Splicing occurs in 95% of the coding RNA. There is scarce information about the spliceosome and mRNA-isoforms in PA, and therefore we carried out proteomic and transcriptomic analysis to identify spliceosome components and mRNA isoforms in PA. Methods: Proteomic profile analysis was carried out by nano-HPLC and mass spectrometry with a quadrupole time-of-flight mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Another notable finding emerging from the transcriptional profiles of adenomas was the enrichment of elements associated with spliceosome observed within three ACs (AC1-3), suggesting a potential role of spliceosome pathway in adrenocortical tumourigenesis, as demonstrated in other benign and malignant tumours [72][73][74] . Interestingly, a different distribution of immune clusters emerged among tissue entities.…”
Section: Discussionmentioning
confidence: 99%
“…Another notable finding emerging from the transcriptional profiles of adenomas was the enrichment of elements associated with spliceosome observed within three ACs (AC1-3), suggesting a potential role of spliceosome pathway in adrenocortical tumourigenesis, as demonstrated in other benign and malignant tumours [72][73][74] . Interestingly, a different distribution of immune clusters emerged among tissue entities.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, due to technical restrictions in regard to tissue samples, we were unable to perform an experiment that may reveal the molecular identity of recurrent CNFPAs from these patients and explain the mechanistic modifications of the machinery of calcium signaling and gene expression of these adenomas. Our research group has identified some elements of the molecular alterations in other studies of pituitary adenomas, including CNFPAs [14,21,37,38]. However, further investigation is needed that traces, longitudinally, the evolution of adenoma recurrence, from the primary tumor to subsequent events of recurrence in patients, and compare them with non-recurrent CNFPAs and healthy tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The ACTH adenoma group overexpresses miR4501; CNFPA upregulates miR582, miR4774, and LINC01351 ; while the GH, TSH, and PRL adenoma cluster overexpresses miR377 and miR136 5 . Upregulation of spliceosome genes and spliceosome proteins, such as SRSF1 , U2AF1 , and RBM42, and changes in CDK18 and THY1 mRNA have been detected in PAs 11 . In vitro experiments of aggressive adenoma tissues unveiled the role of mRNA-146b-5p in suppressing the IRAK4/TRAF6/NF-κB signaling pathway, limiting PA cell progression, and in TMZ-induced chemoresistance in vitro 12 .…”
Section: Advances In Understanding and Managing Pituitary Adenomasmentioning
confidence: 99%